The media and religious authority - Hoover, Stewart M. (Pennsylvania: University Park, 2016)
"Explores how modern means of communication are changing religion, and how contemporary mediations of religion challenge and refine the aspirations and prospects of religious authority"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Mass media -- Religious aspects; Authority -- Religious aspects